Low-Carbon Clean Technology for Waste Energy Recovery in Power Plants Based on Green Environmental Protection - Tian, Yong; Liu, Wen-Jing; Jiang, Qi-jie; Xu, Xin-Ying (Distributed Generation & Alternative Energy Journal, 2021)
With the development of biomass power generation technology, biomass waste has a more excellent recycling value. The article establishes a biomass waste inventory model based on the material flow analysis method and predicts raw material waste’s energy utilization potential. The results show that the amount of biomass waste generated from 2016 to 2020 is on the rise. In 2020, biomass waste’s energy utilization can reach 107,802,300 tons, equivalent to 1,955.28PJ of energy. Through biomass energy analysis and emission analysis, the results show that the biomass waste can generate 182.02 billion kW·h in 2020, which can replace 35.9% of the region’s total power consumption, which is compared with the traditional power generation method under the same power generation capacity. Power generation can reduce SO2 emissions by 250,400 tons, NOx emissions by 399,300 tons, and PM10 emissions by 49,700 tons. Reduce direct economic losses by 712 million yuan. Therefore, Chinese promotion of the recycling of biomass waste and the acceleration of the biomass energy industry’s development is of great significance for reducing pollutant emissions and alleviating energy pressure.